Heat-stress exercise and cooling - Tyler, C. J. (Heat stress in sport and exercise. Thermophysiology of health and performance, 2019)
Athletes regularly adopt cooling strategies before (pre-cooling) and/or during (per-cooling) exercise in the heat to alleviate the extra thermal strain. The most effective cooling interventions involve water immersion, but often lack the practicality desired. Moreover, the effectiveness of practical cooling strategies to improve exercise performance and reduce actual and perceived thermal strain varies. Exercise in the heat places the body under a large thermal strain and although pre- or per-cooling can help, heat illnesses may still occur. The rapid reduction in core body temperature is vitally important to minimise the consequences of any heat illness experienced. This chapter will discuss external and internal cooling strategies that can be adopted before, during, or after exercise undertaken in a hot environment.